Transrectal ultrasound biopsy of the prostate: State of the art and practical guide of tip and tricks (2019)
Introduction Transrectal biopsy of the prostate was described for the first time in 1937, and it was not until 1981 the first transrectal biopsy of the prostate was done using transrectal ultrasound to guide the procedure. Nowadays it is the most popular technique to obtain prostatic tissue when suspecting adenocarcinoma of the prostate, this due to its easy learning curve and to its excellent diagnostic performance. Up to 68% of urologist in the UK do not do prostate biopsy arguing they have not received enough training The aim of this article is to describe the different techniques, the physics of ultrasonography and a practical guide of tips and tricks from a center where we performed up to 1100 transrectal ultrasound biopsies annually, aiming to improve the diagnostic performance and lower the complicacion rates of the biopsy. Methods We performed a search in PubMed, MEDLINE, SciELO using the keywords “Transrectal ultrasound biopsy of the prostate” “tips and tricks” “Transperineal biopsy of the prostate””Magnetic resonance imaging targeted biopsy” “MRI/US fusion biopsy,” and base on the literature review and our experience of more than a thousand biopsies annually we wrote this article. Results TRUS biopsy of the prostate continue to be the first choice in the urologist armamentarium to diagnose the patient with clinical suspicion of prostate cáncer, with a low complication rate, a good diagnostic performance and an easy learning curve. It is necessary to standardized the procedure, perform a doble sextant biopsy, define the best antibiotic prophylaxis, the technique for anesthesia/analgesia. Here we present our practical guide of tips and tricks. Copyright © 2019, Sociedad Colombiana de Urología. Publicado por Thieme Revinter Publicações Ltda., Rio de Janeiro, Brazil. Todos los derechos reservados.